2019
DOI: 10.17116/stomat20199804120
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotic application in the treatment and prevention of peri-implant mucositis

Abstract: Для выполнения поставленной задачи после протезирования несъемными конструкциями на дентальных имплантатах были набраны 42 пациента с перимукозитом при глубине кармана 3-4 мм. Эффективность лечения оцени

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One study reported probiotic therapy without nonsurgical mechanical therapy ( Flichy-Fernández et al, 2015 ), and one study lacked the data of clinical examination of the implant inflammation ( Lauritano et al, 2019 ). The other study was excluded because it was written in Russian ( Ahmedbeyli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported probiotic therapy without nonsurgical mechanical therapy ( Flichy-Fernández et al, 2015 ), and one study lacked the data of clinical examination of the implant inflammation ( Lauritano et al, 2019 ). The other study was excluded because it was written in Russian ( Ahmedbeyli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 10 publications was carefully read and among them, only 4 articles that satisfy the inclusion criteria alone were included [reasons for exclusion are given in Table 1 ]. [ 11 , 21 - 25 ] Finally, a total of four publications fulfilled the inclusion criteria[ 12 , 26 - 28 ] and among them two articles presented with outcomes of two different patient groups. [ 26 , 27 ] Thus, this systematic review and meta-analysis were prepared with data from 6 individual studies [ Figure 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…The severity of peri-implant mucositis was also reduced significantly in a more recent trial using a probiotic combination (L. reuteri DSM 26866, L. rhamnosus DSM 21690, L. bulgaricus DSM21690, and Bifidobacterium animalis ssp. lactis DSM 17741) [68]. Clinical parameters (as determined by PI, GI, BOP, and PD) improved significantly in the test group relative to the control group after 1 month of consumption of probiotics.…”
Section: Probiotics In Peri-implant Diseasesmentioning
confidence: 88%